AcuM and AcuK: The global regulators controlling multiple cellular metabolisms in a dimorphic fungus Talaromyces marneffei. - Tanaporn Wangsanut; Artid Amsri; Thitisuda Kalawil; Panwarit Sukantamala; Juthatip Jeenkeawpieam; Alex Andrianopoulos; Monsicha Pongpom (Public Library of Science (PLoS), 2024)
Talaromycosis is a fungal infection caused by an opportunistic dimorphic fungus Talaromyces marneffei. During infection, T. marneffei resides inside phagosomes of human host macrophages where the fungus encounters nutrient scarcities and host-derived oxidative stressors. Previously, we showed that the deletion of acuK, a gene encoding Zn(2)Cys(6) transcription factor, caused a decreased ability for T. marneffei to defend against macrophages, as well as a growth impairment in T. marneffei on both low iron-containing medium and gluconeogenic substrate-containing medium. In this study, a paralogous gene acuM was deleted and characterized. The ΔacuM mutant showed similar defects with the ΔacuK mutant, suggesting their common role in gluconeogenesis and iron homeostasis. Unlike the pathogenic mold Aspergillus fumigatus, the ΔacuK and ΔacuM mutants unexpectedly exhibited normal siderophore production and did not show lower expression levels of genes involved in iron uptake and siderophore synthesis. To identify additional target genes of AcuK and AcuM, RNA-sequencing analysis was performed in the ΔacuK and ΔacuM strains growing in a synthetic dextrose medium with 1% glucose at 25 °C for 36 hours. Downregulated genes in both mutants participated in iron-consuming processes, especially in mitochondrial metabolism and anti-oxidative stress. Importantly, the ΔacuM mutant was sensitive to the oxidative stressors menadione and hydrogen peroxide while the ΔacuK mutant was sensitive to only hydrogen peroxide. The yeast form of both mutants demonstrated a more severe defect in antioxidant properties than the mold form. Moreover, ribosomal and ribosomal biogenesis genes were expressed at significantly lower levels in both mutants, suggesting that AcuK and AcuM could affect the protein translation process in T. marneffei. Our study highlighted the role of AcuK and AcuM as global regulators that control multiple cellular adaptations under various harsh environmental conditions during host infection. These transcription factors could be potentially exploited as therapeutic targets for the treatment of this neglected infectious disease.